Heat transfer in a geothermal heat-pump system – an analytical assessment. Issue 2 (30th June 2014) - Yang, Y.; Datcheva, M.; König, D.; Schanz, T.
Abstract : A heat transfer model of a vertical borehole heat exchange system (open-loop) is introduced. Outside the borehole, a linearly increasing initial temperature for the ground is employed. Inside the borehole, the heat transfer procedure is divided into passive and active steps. An analytical solution of the heat transfer problem for a system of semi-infinite ground with a finite line source is derived and the open-loop case is discussed. The temperature distribution both inside and outside the borehole is obtained for a long operation time. A model parameter study is performed and the results are discussed. The analytical solutions and parameter study results are also compared with the respective U-tube model (closed-loop system). It is shown that, compared with the U-tube model, the open-loop system can improve the heat exchange system by increasing system effectiveness.